Assessment of autonomic symptoms may assist with early identification of mild cognitive impairment with Lewy bodies. (18th March 2022) - Hamilton, Calum A.; Frith, James; Donaghy, Paul C.; Barker, Sally A. H.; Durcan, Rory; Lawley, Sarah; Barnett, Nicola; Firbank, Michael; Roberts, Gemma; Taylor, John‐Paul; Allan, Louise M.; O'Brien, John; et al.
Abstract: Objectives: Autonomic symptoms are a common feature of the synucleinopathies, and may be a distinguishing feature of prodromal Lewy body disease. We aimed to assess whether the cognitive prodrome of dementia with Lewy bodies, mild cognitive impairment (MCI) with Lewy bodies (MCI‐LB), would have more severe reported autonomic symptoms than cognitively healthy older adults, with MCI due to Alzheimer's disease (MCI‐AD) also included for comparison. We also aimed to assess the utility of an autonomic symptom scale in differentiating MCI‐LB from MCI‐AD. Methods: Ninety‐three individuals with MCI and 33 healthy controls were assessed with the Composite Autonomic Symptom Score 31‐item scale (COMPASS). Mild cognitive impairment patients also underwent detailed clinical assessment and differential classification of MCI‐AD or MCI‐LB according to current consensus criteria. Differences in overall COMPASS score and individual symptom sub‐scales were assessed, controlling for age. Results: Age‐adjusted severity of overall autonomic symptomatology was greater in MCI‐LB (Ratio = 2.01, 95% CI: 1.37–2.96), with higher orthostatic intolerance and urinary symptom severity than controls, and greater risk of gastrointestinal and secretomotor symptoms. MCI‐AD did not have significantly higher autonomic symptom severity than controls overall. A cut‐off of 4/5 on the COMPASS was sensitive to MCI‐LB (92%) but not specific to this (42% specificity vs. MCI‐AD and 52% vs. healthy controls). Conclusions: Mild cognitive impairment with Lewy bodies had greater autonomic symptom severity than normal ageing and MCI‐AD, but such autonomic symptoms are not a specific finding. The COMPASS‐31 may therefore have value as a sensitive screening test for early‐stage Lewy body disease. Key points: Autonomic symptoms are common in prodromal dementia with Lewy bodies (DLB) compared to normal ageing. Gastric and secretory symptoms are more commonly reported. Orthostatic and urinary symptoms are reported as more severe. Dysautonomia is a sensitive finding for prodromal DLB.